Implementation of Bound Morpheme Through A Text to The Students of HKBP Nommensen Pematangsiantar University - Munthe, Melda Veby Ristella (Future Science / FSH-PH Publications, 2023)
Words are composed of morphemes. The notion that morphemes are words is not necessarily true. While some single morphemes can function as words, some words have two or more morphemes. Furthermore, it is wrong to consider morphemes to be syllables. In contrast, many words only have one syllable and two morphemes; examples are